Beyond Katrina : a meditation on the Mississippi Gulf Coast - Trethewey, Natasha D., 1966- (University of Georgia Press, 2010)
"Trethewey spent her childhood in Gulfport, where much of her mother's extended family, including her younger brother, still lives. As she worked to understand the devastation that followed the hurricane, Trethewey found inspiration in Robert Penn Warren's book Segregation: The Inner Conflict in the South, in which he spoke with southerners about race in the wake of the Brown decision, capturing an event of wide impact from multiple points of view. Weaving her own memories with the experiences of family, friends, and neighbors, Trethewey traces the erosion of local culture and the rising economic dependence on tourism and casinos. She chronicles decades of wetland development that exacerbated the destruction and portrays a Gulf Coast whose citizens--particularly African Americans--were on the margins of American life well before the storm hit."--Publisher description.